2018
DOI: 10.1007/s12192-017-0832-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of multiple small heat shock protein genes in spruce budworm, Choristoneura fumiferana (L.)

Abstract: Fifteen small heat shock protein (sHSP) genes were identified from spruce budworm, Choristoneura fumiferana (L.), an important native forest pest in North America. The transcript levels of each CfHSP were measured under non-stress conditions in all life stages from egg to adult and in five different larval tissues. CfHSP transcript levels showed variation during development, with highest levels in adults and lowest in eggs. Most CfHSP transcripts are highly expressed in larval fat body and Malpighian tubules; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…Similar to the findings in other insects 5,25,27 , the expression of several Hsp genes was induced by heat-shock in S. frugiperda cell line, embryos, and larval tissues. Since heat-inducible expression of Hsp gene was achieved by HSF binding to the HSEs located in the promoters of Hsp genes 29 , the variation of heat-inducibility among SfHsp gene is likely associated with the number of HSEs in their promoters.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to the findings in other insects 5,25,27 , the expression of several Hsp genes was induced by heat-shock in S. frugiperda cell line, embryos, and larval tissues. Since heat-inducible expression of Hsp gene was achieved by HSF binding to the HSEs located in the promoters of Hsp genes 29 , the variation of heat-inducibility among SfHsp gene is likely associated with the number of HSEs in their promoters.…”
Section: Discussionsupporting
confidence: 86%
“…Expression of Hsp from a wide range of insect species have been reported to be induced and modulated by abiotic stressors, including extreme temperature 3-5 , ultraviolet radiation 6,7 , pesticides 8,9 , heavy metals 10,11 , desiccation 12-14 , starvation 15,16 , and anoxia/hypoxia 17-19 , as well as several biotic insults, including parasites 20,21 , pathogens 22,23 , and high population density 24 . In recent years, the availability of both transcriptome and genome data greatly contributed to the identification of an increasing number of Hsp genes from diverse insect species and promoted their functional studies 5,9,[25][26][27] . However, information of Hsp genes from a destructive insect pest, Spodoptera frugiperda, is still limited 23,28 .The stress-inducible expression of Hsp gene is conferred by binding of heat-shock factor (HSF) to heat-shock elements (HSEs), which consists of arrays of the 5-bp unit NGAAN arranged as inverted repeats in the promoter region 29 .…”
mentioning
confidence: 99%
“…The large HSP superfamily was commonly classified into several families based on their molecular weight and homologous relationship, including HSP100, HSP90, HSP70, HSP60, HSP40, and HSP20 (Garrido et al, 2012). Since firstly discovered in D. melanogaster larvae, HSPs in many insects have already been identified as heat stress-related factors (Ritossa, 1962;Quan et al, 2017;Guo and Feng, 2018;Wang et al, 2019). In the current study, 15 HSPs were upregulated by heat treatment in M. alternatus.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified 15 sHSP genes in the SBW transcriptomes, including CfHSP20.3, which has no expression during development and may be a pseudogene (Quan et al 2018). Phylogenetic analysis indicated that at least five of these sHSPs are SBW specific.…”
Section: Introductionmentioning
confidence: 99%